A Comparison Investigation on Cylinder Test in Different Ambient Media by Experiment and Numerical Simulation - Fan Zhang; Fei Shen; Biaobiao Li; Baohui Yuan; Bing Li (International Journal of Aerospace Engineering)
When the detonation reaction occurs after the charge in the warhead is ignited, the propagation of the detonation wave and the expansion of the detonation product will interact with the wrapped metallic shell and cause the shell material to accelerate, extremely deform, and eventually rupture, which is a typical strong fluid-structure interaction problem. In this paper, a comparison investigation on a cylinder test in different ambient media was implemented by experiment and numerical simulation, respectively. In the experimental test, the attention was paid to discussing the differences of the accelerating process of the cylinder metal wall, the expansion modes, and the fragment shape of the cylinder due to the medium with different shock wave impedance which surrounds the cylinder shell. For the numerical simulation, a coupling scheme of a meshless method and finite element method called the coupled finite element material point method was used to reproduce the cylinder expansion problem driven by explosive sliding detonation where the interaction between the cylinder wall and the explosive/detonation product is enforced by using a point-to-surface contact scheme to accurately achieve contact and separation between material particles and finite elements. Lastly, the macroscopic and microscopic states of the cylinder failure were compared and discussed for further discussion.